PELATIHAN PEMBUATAN SUPLEMEN HERBAL IMMUNOMODULATOR PADA SANTRI PUTRI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO - Dewi Ratih Tirto Sari; Ana Maria Ulfa; Eliyawati Eliyawati; Lailatus Sarifah; Siti Dina Mega Arofah; Pahirah Pahirah; Riyatul Fitraya; Fadilatul Aini (LP2M Universitas Ibrahimy, 2024)
Acute respiratory infection is a health problematic in Islamic boarding school. Lack of student awareness in maintaining health causes an increase in acute respiratory infections. This community service aims to increase the knowledge, skills and awareness of students in improving immunity and preventing acute respiratory infection. The method used is participatory action research (PAR), which is divided into four stages, namely focus group discussions, education, making herbal supplements, and evaluation. Focus group discussion was participated by some element, including coordinator of santri husada, santri husada, basic health service and students. Education was presented as lectures, discussion and consultation about immunity elevation. Education was conducted in several days for student in A1, A2, B, and M’hadul Quran dormitory to encourage more students. The next step was training to make herbal supplement, which attended by 42 students. The Forty-two student were divided into six groups to make herbal drink and instant supplement drink. Based on training evaluation, the education and training increased the knowledge and skill of participants. In summary, this activity increase health immune knowledge and supplement making of students.